Comparison of oral itasetron with oral ondansetron: results of a double-blind, active-controlled phase II study in chemotherapy-naive patients receiving moderately emetogenic chemotherapy - Goldschmidt, Hartmut; Salwender, Hans; Egerer, Gerlinde; Kempe, Rudolf; Voigt, Thor (Anti-cancer drugs, 1997)
Itasetron hydrochloride is a new 5-hydroxytryptamine3 (5-HT3) antagonist. Experimental Investigations show that orally it is rapidly absorbed (about 90 min), is highly bioavailable (greater than 90%), has a long half-life (about 12 h) and is more potent (about 10 times) in animal models than ondansetron, currently standard therapy for the prophylactic control of chemotherapy induced nausea and vomiting. This paper describes the results of a study designed to assess the efficacy and tolerability of five (0.5, 1, 2, 4 and 8 mg) twice-daily doses of itasetron hydrochloride, in comparison with 8 mg b.i.d. ondansetron. Assessments were made in patients (n = 104) with histologically confirmed cancer (excluding head and neck tumors) and about to receive their first course of moderately emetogenic chemotherapy. Itasetron hydrochloride demonstrated comparable efficacy to ondansetron; no statistically significant between-group differences were observed in the primary (complete response rate) or secondary (nausea and delayed emesis) efficacy criteria. Adverse events were similar in type and incidence across all treatment groups, and were those expected for this therapeutic class. The tolerability of itasetron hydrochloride was assessed as ‘very good’ or ‘rather good’ by 81% of patients and 89% of physicians. In conclusion, itasetron hydrochloride is effective and well tolerated in patients receiving moderately emetogenic chemotherapy. Oral doses of 1 mg b.l.d. or above will be used in further clinical studies.
Gesehen am 24.04.2025